2019
DOI: 10.1021/acs.jctc.8b01205
|View full text |Cite
|
Sign up to set email alerts
|

Reference Energies for Double Excitations

Abstract: Excited states exhibiting double excitation character are notoriously di cult to model using conventional singlereference methods, such as adiabatic time-dependent density-functional theory (TD-DFT) or equation-of-motion coupled cluster (EOM-CC). In addition, these states are typical experimentally "dark" making their detection in photo-absorption spectra very challenging. Nonetheless, they play a key role in the faithful description of many physical, chemical, and biological processes. In the present work, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
420
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 182 publications
(452 citation statements)
references
References 437 publications
(943 reference statements)
30
420
2
Order By: Relevance
“…For all the transitions of the QUEST#3 set, we reported at least CCSDT/aug-cc-pVTZ (sometimes with basis set extrapolation) and CC3/aug-cc-pVQZ transition energies as well as CC3/aug-cc-pVTZ oscillator strengths for each dipole-allowed transition. Pursuing our previous benchmarking efforts, 47,50 we confirmed that CC3 almost systematically delivers transition energies in agreement with higher-level theoretical models (±0.04 eV) except for transitions presenting a dominant double excitation character (see Fig. 3).…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…For all the transitions of the QUEST#3 set, we reported at least CCSDT/aug-cc-pVTZ (sometimes with basis set extrapolation) and CC3/aug-cc-pVQZ transition energies as well as CC3/aug-cc-pVTZ oscillator strengths for each dipole-allowed transition. Pursuing our previous benchmarking efforts, 47,50 we confirmed that CC3 almost systematically delivers transition energies in agreement with higher-level theoretical models (±0.04 eV) except for transitions presenting a dominant double excitation character (see Fig. 3).…”
Section: Methodssupporting
confidence: 83%
“…It is also noteworthy that CCSDT and CC3 are also able to detect the presence of double excitations, a feature that is absent from both CCSD and CC2. 50 It is also important to mention the recent rejuvenation of the second-and third-order algebraic diagrammatic construction [ADC (2) 51 and ADC(3) 52,53 ] methods that scale as N 5 and N 6 , respectively. These methods are related to the older second-and third-order polarization propagator approaches (SOPPA and TOPPA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have developed two sets of theoretical best estimates (TBEs) of FCI quality for the vertical transition energies of small closed-shell compounds. 20,21 (See Ref. 24 for a recent review.)…”
Section: Introductionmentioning
confidence: 99%
“…24,43 However, similar to adiabatic TD-DFT, [44][45][46][47] the static version of BSE cannot describe multiple excitations. [48][49][50] A significant limitation of the BSE formalism, as compared to TD-DFT, lies in the lack of analytical nuclear gradients (i.e., the first derivatives of the energy with respect to the nu-clear displacements) for both the ground and excited states, 51 preventing efficient studies of excited-state processes (e.g., chemoluminescence and fluorescence) associated with geometric relaxation of ground and excited states, and structural changes upon electronic excitation. [52][53][54][55] While calculations of the GW quasiparticle energy ionic gradients is becoming increasingly popular, [56][57][58][59][60][61] only one pioneering study of the excited-state BSE gradients has been published so far.…”
mentioning
confidence: 99%